2004
DOI: 10.1111/j.1751-1097.2004.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Intracellular Aggregation of Hypericin and the Impact on its Photocytotoxicity in PAM 212 Murine Keratinocytes

Abstract: We have assessed photoinduced toxicity of hypericin in PAM 212 murine keratinocytes and the relationship between concentration, incubation time and light fluence to evaluate the effect of intracellular aggregation at high concentrations. Confocal microscopy was used to establish the subcellular localization of hypericin at 5 and 50 μM and incubation times of 1 and 3 h. From fluorescence uptake time course studies, intracellular hypericin was demonstrated to exist predominantly in the monomeric form for up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The corresponding ratios for 2 μ m incubation are 1.45 and 3.4. This discrepancy can be attributed to increased intracellular aggregation like we have previously seen for hypericin which is expected to be higher at higher uptakes. Also, as we have shown in our previous work for MCF7 and MDA‐MB‐231 cells , different cell lines have dissimilar tolerances and diverse defense mechanisms to PDT.…”
Section: Discussionmentioning
confidence: 55%
“…The corresponding ratios for 2 μ m incubation are 1.45 and 3.4. This discrepancy can be attributed to increased intracellular aggregation like we have previously seen for hypericin which is expected to be higher at higher uptakes. Also, as we have shown in our previous work for MCF7 and MDA‐MB‐231 cells , different cell lines have dissimilar tolerances and diverse defense mechanisms to PDT.…”
Section: Discussionmentioning
confidence: 55%
“…Activating it with light, or UV‐A, in the presence of molecular oxygen leads to the generation of reactive oxygen species (ROS) and these ultimately kill the cells (Milanesio et al., 2001; Dolmans et al., 2003). In addition, hypericin accumulates in the endoplasmic reticulum (Agostinis et al., 2002), Golgi (Uzdensky et al., 2001; Theodossiou et al., 2006), lysosomes (Siboni et al., 2002; Theodossiou et al., 2004) and mitochondria (Ali and Olivo, 2002). Although earlier reports suggested that hypericin was excluded from mitochondria, it clearly affects cytochrome c release which induces caspase‐dependent apoptosis and other forms of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Following light excitation, HYP exhibits enhanced in vitro cytotoxicity (5–8) attributed to various ROS (7–12). The photocytotoxic action of HYP is highly dependent on its locoregional accumulation within the cell; previous studies on the subcellular localization of HYP indicate a selective affinity to lipid membranes in general (13).…”
Section: Introductionmentioning
confidence: 99%
“…The photocytotoxic action of HYP is highly dependent on its locoregional accumulation within the cell; previous studies on the subcellular localization of HYP indicate a selective affinity to lipid membranes in general (13). More specifically, HYP has been found to accumulate in the endoplasmic reticulum (ER) and Golgi (14), lysosomes (6,15) and mitochondria (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation